Nephroprotective effect of atorvastatin at a dose of 80 mg in patients with ST-segment elevation myocardial infarction with an invasive treatment strategy - A. D. Gavrilko; E. M. Mezhonov; S. V. Shalaev; D. V. Krasheninin (Рациональная фармакотерапия в кардиологии)
Aim. To study the effectiveness of atorvastatin 80 mg, prescribed immediately prior emergency endovascular intervention, in reducing the incidence of acute kidney injury (AKI) defined by сontrast-induced nephropathy (CIN) and by Kidney Disease: Improving Global Outcomes (KDIGO) criteria in patients with ST-segment elevation myocardial infarction (STEMI).Material and methods. The study included 386 patients with STEMI. Main group patients immediately prior to sheath insertion took atorvastatin at a high dose (80 mg). The control group was not prescribed statins before the intervention. In both groups, further statin therapy in the postoperative period was not regulated by the study protocol and was prescribed taking into account current guidelines. In order to equalize the groups according to the main clinical indicators, propensity score matching was carried out, as a result of which new comparison groups of 86 patients each were formed. In order to assess the nephroprotective properties, the following end points were selected: the incidence of AKI according to the CIN and KDIGO criteria, the frequency of serum creatinine level recovery to initial values on the 7th day.Results. In the study sample, the median glomerular filtration rate (GFR) on admission was 86,5 [70,0-97,0] ml/min/1,73 m2. There were 22 (12,7%) and 15 (8,7%) patients with GFR<60 ml/1,73 m2 at admission and kidney pathology, respectively. The median volume of contrast injected during coronary angiography (CAG) and percutaneous coronary intervention (PCI) was 100 [90-200] ml, while there were 8 (4,7%) patients in whom the volume of contrast injected exceeded 3,7xGFR. In the group of patients receiving atorvastatin before the intervention, the incidence of AKI was significantly lower according to CIN criteria as follows: 9 (10,5%) vs 21 (24,4%) (p=0,016, odds ratio (OR) (95% confidence interval (CI) — 0,36 (0,16-0,85)), while in case of diagnosis according to KDIGO criteria there was no significant difference: 6 (7,0%) vs 13 (15,1%) (p=0,143, OR (95% CI) — 0,42 (0,15-1,17)).The frequency of serum creatinine level recovery to initial values on the 7th day was higher in the main group: 57 (66,3%) vs 43 (50,6%) (p=0,037, OR (95% CI) — 1,92 (1,04-3,56)). Inhospital mortality was higher in the control group: 6 (7,0%) vs 1 in the main group (1,2%) (p=0,120, OR (95% CI) — 0,17 (0,02-1,47)).Conclusion. The use of atorvastatin at a dose of 80 mg immediately before emergency coronary angiography in patients with STEMI, in comparison with the traditional statin prescription in the postoperative period, reduces the risk of AKI according to the CIN criteria, and also improves renal function.